Clinical researchDo plasma leptin levels predict diastolic dysfunction in patients with hypertension? - Tatli, Ersan; Aktoz, Meryem; Altun, Armağan (Archives of Medical Science, 2009)
Introduction: Increased plasma leptin levels were showed in a number of cardiac problems such as hypertension, left ventricular hypertrophy, coronary artery disease and acute myocardial infarction. The possibility that leptin plays a role in the cardiovascular system was strengthened by the evidence that chronic leptin infusion had been shown to increase heart rate and blood pressure through stimulation of sympathetic nervous system activity. However, the relationship between increased plasma leptin levels and diastolic dysfunction hasn’t been exactly investigated so far. Thus, we investigated relation between plasma leptin levels and diastolic dysfunction in patients with hypertension. Material and methods: Sixty male patients with newly diagnosed essential hypertension were consecutively included in the study. Hypertensive patients were divided into two groups according to Doppler echocardiographic parameters as patients with diastolic dysfunction (group I, n = 38) and without diastolic dysfunction (group II, n = 22). Both groups were compared patients’ characteristics, plasma leptin levels, glucose, insulin, insulin resistance and thyroid hormones. Results: There were no significant differences between patients’ characteristics, fasting insulin, glucose, insulin resistance, thyroid hormones. Echocardiographic evaluation showed similar values of septal and posterior wall thickness, left ventricular end-systolic and end-diastolic diameters, fractional shortening and ejection fraction in both groups. Plasma leptin levels were also found similarly in both groups (group I, 40.6 ±18.4 ng/ml vs. group I, 36.7 ±20.7 ng/ml, p = 0.650). Conclusions: We suggested that leptin levels didn’t predict diastolic dysfunction in patients with hypertension.